2020
DOI: 10.1002/mabi.202000024
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the In Vivo Degradation of Tissue Engineering Implants by Use of Supramolecular Radiopaque Biomaterials

Abstract: For in situ tissue engineering (TE) applications it is important that implant degradation proceeds in concord with neo‐tissue formation to avoid graft failure. It will therefore be valuable to have an imaging contrast agent (CA) available that can report on the degrading implant. For this purpose, a biodegradable radiopaque biomaterial is presented, modularly composed of a bisurea chain‐extended polycaprolactone (PCL2000‐U4U) elastomer and a novel iodinated bisurea‐modified CA additive (I‐U4U). Supramolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Previous studies investigating in vitro and in vivo micro‐CT imaging and monitoring degradation of hydrogel or polymeric scaffolds have generally used greater contrast agent concentrations, including 100 m m Gd 2 O 3 NPs, [ 28 ] 80 m m (≈13.6 wt%) Au NPs, [ 29 ] 20 wt% Au NPs, [ 62 ] 100 mg mL −1 iohexol (≈365 m m iodine), [ 30 ] and 11.4 wt% (≈500 m m ) iodine. [ 63 ] Of particular note, 50 m m TaO x NPs were reported to provide sufficient signal/noise within tissue phantoms for clinical CT imaging. [ 64 ] On the other hand, another study reported in vivo micro‐CT imaging of 3D‐printed gelMA + Au scaffolds comprising 0.16 m m Au NPs, [ 38 ] but did not report X‐ray attenuation in Hounsfield units (HU) making interpretation difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating in vitro and in vivo micro‐CT imaging and monitoring degradation of hydrogel or polymeric scaffolds have generally used greater contrast agent concentrations, including 100 m m Gd 2 O 3 NPs, [ 28 ] 80 m m (≈13.6 wt%) Au NPs, [ 29 ] 20 wt% Au NPs, [ 62 ] 100 mg mL −1 iohexol (≈365 m m iodine), [ 30 ] and 11.4 wt% (≈500 m m ) iodine. [ 63 ] Of particular note, 50 m m TaO x NPs were reported to provide sufficient signal/noise within tissue phantoms for clinical CT imaging. [ 64 ] On the other hand, another study reported in vivo micro‐CT imaging of 3D‐printed gelMA + Au scaffolds comprising 0.16 m m Au NPs, [ 38 ] but did not report X‐ray attenuation in Hounsfield units (HU) making interpretation difficult.…”
Section: Resultsmentioning
confidence: 99%
“…For application of biodegradable scaffolds in large preclinical animal models and human patients, in vivo biodegradation has to be adjusted to balance with a tissue-healing rate. 46 The scaffolds’ in vivo degradation rate was preoptimized by controlling the surface porosity, as demonstrated in previous studies, 47,50 resulting in full degradation in the rabbit model by 12 weeks. However, the in vivo degradation rate of polyester scaffolds can be affected by local biological, chemical, and physical environments, 28,50 necessitating further adjustments for large animal models or human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) is an efficient and accurate technique to investigate radical and oxidative stresses [ 83 ]. Ultrasound elasticity imaging (UEI) can be used to characterise the structural, functional, and compositional changes of biodegradable scaffolds via phase-sensitive speckle tracking [ 84 , 85 ]. Several non-invasive and non-destructive techniques to investigate parameters such as a scaffold’s pH value, distribution, and cell viability are: (i) confocal laser scanning microscopy (CLSM); (ii) nuclear magnetic resonance (NMR); (iii) optical coherence microscopy (OCM); (iv) optical coherence tomography (OCT).…”
Section: Biodegradation Mechanisms Of Polymeric-based Scaffoldsmentioning
confidence: 99%